Profiling of phenolic compounds of fruit peels of different ecotype bananas derived from domestic and imported cultivars with different maturity - Zhang, Jing; Wang, Yongfen; Yang, Baoming; Li, Yongping; Liu, Lina; Zhou, Weie; Zheng, Si-Jun (MDPI, 2022)
Banana is one of the most produced and consumed fruits in the world and its fruit peel accounts for about 40% of the total fresh quantity of ripe fruit, which is usually regarded as waste and poses serious environmental hazards. However, it is a promising source of natural bioactive compounds including phenolic compounds. Determination of the phenolic compounds in fruit peel from different cultivars and subgroups over a range of maturities provides convincing information for making full use of them. This study developed a sensitive and reliable analytical method ultra-high performance liquid chromatography coupled with lectrospray ionization tandem mass spectrometry (UPLC-MS/MS) for measuring phenolic compounds in fruit peel from different ecotype cultivars and subgroups with different maturity. The results showed that quinic acid had the highest concentration ratio among the main phenolic compounds in the green/ripe peel of all banana cultivars; among all banana cultivars, the total phenolic compound contents of green banana peel were significantly higher than that of ripe banana peel; the total phenolic compound contents in the green/ripe fruit peel of non-dessert bananas were significantly higher than that of dessert bananas (green: non-dessert banana 1.48 ± 0.44 mg/g vs. dessert banana 0.97 ± 0.12 mg/g; ripe: non-dessert banana 0.26 ± 0.13 mg/g vs. dessert banana 0.19 ± 0.06 mg/g). These data provide a basis for the rational utilization of phenolic compound extractions from banana peel with huge biomass in the next step.